The Implementation of Problem-Based Learning for Students' English-Speaking Ability - Helda Oktaviani; Siti Suharsih; Yudi Juniardi (English Education Department, Postgraduate, Universitas Sultan Ageng Tirtayasa, Indonesia, 2024)
This research explores the perceptions of English teachers at SMPN 21 Kota Serang regarding implementing problem-based learning in their classes. The PBL model is used to teach speaking in class VIII D at SMPN 21 Kota Serang. The lack of motivation is the most significant reason for EFL students' English-speaking proficiency. A PBL model teaching approach can increase students' motivation to learn English. Implementing the PBL model can help students feel involved and challenged to solve problems to increase their motivation to learn. This research uses a qualitative case study as its research methodology to gain an in-depth understanding of emerging problems. English teachers in class VIII D were observed and interviewed about implementing problem-based learning. The findings of this research reveal that teachers who implement problem-based learning have succeeded in providing significant changes to students' English-speaking abilities and have motivation to speak English. Therefore, the researcher found that implementing problem-based learning in English language learning was successful in helping motivate students.